Developing A Punching Exercise Tool For Boxing - David Iqroni; Donny Setiawan (Journal of Coaching and Sports Science, 2022)
This study aims to produce an exercise tool that can be used to train the speed of punches and reactions for boxing martial arts athletes. The research method used was Research and Development. The steps of this research were adapted from Sugiyono's research steps which consisted of thirteen steps. However, the researcher only adapted ten steps following the objectives of this development research. The researchers conducted a small group trial in the boxing gym of Sasana Kota Baru Jambi on five respondents. Also, the researchers conducted a large group trial at the boxing gym of Sasana Kota Baru Jambi on ten respondents or the entire population. The feasibility assessment result from the material expert was 100 percent (highly feasible), and the media expert was 98.88 percent (highly feasible). The results of the small group trial obtained an assessment score of 91.13 percent (highly feasible), and the large group trial obtained an assessment score of 91.39 percent (highly feasible). These results indicate that the developed tool is feasible and can be used to practice and train the speed of punches and reactions.